2017
DOI: 10.1534/genetics.117.300390
|View full text |Cite
|
Sign up to set email alerts
|

The Hybrid Incompatibility Genes Lhr and Hmr Are Required for Sister Chromatid Detachment During Anaphase but Not for Centromere Function

Abstract: Crosses between females and males produce hybrid sons that die at the larval stage. This hybrid lethality is suppressed by loss-of-function mutations in the () or in the () genes. Previous studies have shown that Hmr and Lhr interact with heterochromatin proteins and suppress expression of transposable elements within It also has been proposed that Hmr and Lhr function at the centromere. We examined mitotic divisions in larval brains from and single mutants and; double mutants in In none of the mutants did we … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
35
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(39 citation statements)
references
References 62 publications
4
35
0
Order By: Relevance
“…Consistent with its known function we found the GO terms such as chromatin silencing, histone modification and positive regulation of chromatin organization for HP1a AP . For HMR AP , we found the GO terms heterochromatin organization involved in chromatin silencing, telomere maintenance, mitotic sister chromatid segregation and nucleus organization, which were consistent with the observed phenotypes of HMR mutations in Drosophila melanogaster (13, 15, 22, 33, 34). This proximity-based proteome also strengthens the hypothesis that HMR localizes in between dCenpA and HP1a containing chromatin as components of both domains are found in proximity of HMR.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…Consistent with its known function we found the GO terms such as chromatin silencing, histone modification and positive regulation of chromatin organization for HP1a AP . For HMR AP , we found the GO terms heterochromatin organization involved in chromatin silencing, telomere maintenance, mitotic sister chromatid segregation and nucleus organization, which were consistent with the observed phenotypes of HMR mutations in Drosophila melanogaster (13, 15, 22, 33, 34). This proximity-based proteome also strengthens the hypothesis that HMR localizes in between dCenpA and HP1a containing chromatin as components of both domains are found in proximity of HMR.…”
Section: Resultssupporting
confidence: 84%
“…Notably, the quantitation of more than 120 interphase centromeres indicated that 57% of all centromere foci overlap with HMR foci. This suggests that the localization of HMR to the centromere is either cell cycle regulated or specific for a subset of centromeres (Figure 1B), which may explain the differences observed when staining HMR in different tissues (13, 15). Another observation that is difficult to reconcile with the clustered staining of HMR in cells is the fact that ChIP-seq data suggest HMR binding along the euchromatic arms often at boundaries between HP1a containing heterochromatin and actively transcribed genes (20).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Biochemical studies have shown that HMR and LHR physically bind to each other and function together in a complex with Heterochromatin Protein 1 (HP1a) (Brideau et al 2006; Thomae et al 2013;Satyaki et al 2014). Null mutants of Hmr and Lhr in D. melanogaster show defects in sister chromatid detachment during anaphase (Blum et al 2017) and show de-repression of transcripts from several families of transposable elements and satellite DNA (Thomae et al 2013;Satyaki et al 2014). Both proteins are overexpressed in hybrid F1 males, and hybrids display a pattern of de-repression of transcripts from transposable elements and satellite DNA (Thomae et al 2013;Satyaki et al 2014).…”
Section: Introductionmentioning
confidence: 99%
“…26 Probe sequences are provided in the Reagent Table. 27 28 Immunofluorescence on mitotic chromosome spreads 29 A protocol described in (Blum et al 2017) was used to conduct immunofluorescence on 30 mitotic chromosome spreads. Briefly, larval brains from third instar larvae were 31 dissected and incubated in 30μL of 0.5% sodium citrate on Superfrost Plus Microscope 32…”
mentioning
confidence: 99%